(untitled) (Педагогіка вищої та середньої школи, 2008)
In the article the basic aspects of professionally-orientation work are examined on the lessons of labour studies in modern terms. The role of teacher is shown in forming of professional self-determination of students at the study of discipline the «Labour studies» in secondary comprehensive schools.